PENGARUH SUPLEMENTASI VITAMIN D TERHADAP NILAI PENGUKURAN FEV1/ FVC PADA PENDERITA ASMA TERKONTROL SEBAGIAN - Adyan Donastin; Arief Bakhtiar; Daniel Maranatha (Jurnal Ilmu Kesehatan dan Kesehatan, 2017)
Background:Airflow resistance in asthma caused by changes in the airways that is bronchoconstriction,airway edema, airway hyperresponsiveness and airway remodeling. Vitamin D supplementation is expectedto raise the value of the measurement of FEV1/ FVC in patients with asthma controlled in part through therole of vitamin D in terms of antiviral effects, atopic response, response improvement steroid and preventairway remodeling process.Objective:Comparing the measurement values of FEV1/ FVC in patients withasthma controlled most of which do not get supplemental vitamin D than getting supplemental vitaminD.Methods:This study is a randomized experimental simple study. This research was conducted in drSoetomo Hospital from June to July 2015. The sampling technique using consecutive sampling. Sampleswere divided into two groups each consisting of 14 samples which have earned a combined therapy ofinhaled corticosteroids and LABA. The control group that was not given additional vitamin Dsupplementation and the treatment group were given supplements of vitamin D for 1 month. Measurementand main result:Testing of data distribution using the ShapiroWilk method because the sample size is lessthan 50. The result of the difference in FEV1 / FVC with a paired sample t - test is known that in the controlgroup (not given additional vitamin D supplements) did not occur significant difference (p = 0.219> 0.05),while the treatment group (given additional vitamin supplements D) proved significant difference (p = 0.020<0.05) where the value of FEV1 / FVC after being given additional vitamin D supplements increased to96.071% of the initial conditions is 84.786%.Conclusions:The measurement values of FEV1/ FVC in patientswith asthma controlled most of which get vitamin D supplementation are the most significant increasecompared to the control group who did not receive supplementation ofvitamin D.